2013
DOI: 10.1371/journal.pbio.1001717
|View full text |Cite
|
Sign up to set email alerts
|

HDAC4 Reduction: A Novel Therapeutic Strategy to Target Cytoplasmic Huntingtin and Ameliorate Neurodegeneration

Abstract: HDAC4 histone deacetylase is found to associate with huntingtin in a polyQ-length dependent manner. Reduction of HDAC4 levels in mouse models of Huntington's disease (HD) delays cytoplasmic aggregation in the brain and improves the molecular pathology of HD, providing a potential new therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
153
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(164 citation statements)
references
References 66 publications
(83 reference statements)
9
153
0
Order By: Relevance
“…Histone deacetylases 1 and 2 usually form a heterodimer in multiprotein chromatin remodeling complexes with other co-factors, such as Sin3a, NuRD and REST/CoREST, which are important both for enzymatic activity and specificity of DNA/chromatin interactions (Dovey et al, 2010;Ji et al, 2014;Jia et al, 2012;Lagger et al, 2002;Mielcarek et al, 2013;Reichert et al, 2012;Trivedi et al, 2007;Tsai and Seto, 2002;Zimmermann et al, 2007). A surprise finding from our study was that Sin3a LOF not only recapitulated many of the defects observed with Hdac1/2 LOF, but led to more profound defects at an earlier stage of lung development.…”
Section: Discussionsupporting
confidence: 47%
“…Histone deacetylases 1 and 2 usually form a heterodimer in multiprotein chromatin remodeling complexes with other co-factors, such as Sin3a, NuRD and REST/CoREST, which are important both for enzymatic activity and specificity of DNA/chromatin interactions (Dovey et al, 2010;Ji et al, 2014;Jia et al, 2012;Lagger et al, 2002;Mielcarek et al, 2013;Reichert et al, 2012;Trivedi et al, 2007;Tsai and Seto, 2002;Zimmermann et al, 2007). A surprise finding from our study was that Sin3a LOF not only recapitulated many of the defects observed with Hdac1/2 LOF, but led to more profound defects at an earlier stage of lung development.…”
Section: Discussionsupporting
confidence: 47%
“…14 -3-3 association restricts the binding of HDAC4 to importin-␣, indicating that inhibition of HDAC nuclear import likely occurs via occlusion of the NLS (35). A similar regulatory mechanism has been reported for other proteins, including Cdc25 in Xenopus XTC cells and ATXN1 in neurons (21,124).…”
Section: Hdac5-although Numerous Hdac5supporting
confidence: 57%
“…Huntington's disease is caused by the mis-folding of the huntingtin protein, and its pathology is associated with the formation of both nuclear and cytoplasmic aggregates (160). HDAC4 has emerged as a possible promising target for the treatment of Huntington's disease because of its association with the huntingtin protein and its ability to influence the formation of cytoplasmic aggregates (21). As HDAC4 localization is determined by its phosphorylation status, these signaling pathways could be exploited to promote the nuclear retention of HDAC4 in order to limit the formation of cytoplasmic aggregates associated with Huntington's disease pathogenesis.…”
Section: Hdac5-although Numerous Hdac5mentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclopropanation of the methyl cinnamate derived from 1 as previously described, 6 followed by deprotonation of the racemic intermediate 2 using LDA (1.1−3 equiv) and quenching with an appropriate electrophile (MeI, CCl 4 or NFSI) 14 afforded the tetrasubstituted cyclopropane. The desired isomer was isolated by flash chromatography.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%